ENHANCING THE QUALITY OF EMERGENCY ADMISSION CLERKING IN NEUROSURGERY: A COMPARATIVE STUDY OF TRADITIONAL METHODS VERSUS A SURGICAL CLERKING PROFORMA - Kazmi, Waseem Ahmed Shah; Ushna Khan Durrani,; Zara Rathod,; Aya Abdelhamid Elshalakany, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Accurate and comprehensive documentation during emergency admissions is crucial for ensuring patient safety. This is especially important in high-risk environments such as neurosurgery. Traditional freehand clerking methods often result in incomplete or inconsistent records, potentially compromising patient care. This study aimed to evaluate the impact of introducing a structured surgical clerking proforma on the quality of emergency admission clerking in a tertiary care neurosurgery unit. Methods: A three-phase comparative audit was conducted, comprising an initial audit of traditional clerking methods (Cycle 1), the implementation of a surgical clerking proforma, and a subsequent re-audit using the proforma (Cycle 2). Data were collected retrospectively from 40 patient records in Cycle 1 and prospectively from 30 patient records in Cycle 2. The completeness of documentation was assessed across 31 key parameters, and statistical significance was determined using paired t-tests on simulated data. Results: The introduction of the surgical clerking proforma resulted in significant improvements in documentation completeness, particularly for parameters such as the Consultant Responsible and Reviewing Doctor, which saw increases of 30% and 32.5%, respectively (p<0.05). These improvements underscore the effectiveness of the proforma in standardizing and enhancing the reliability of clinical documentation. Conclusion: The structured surgical clerking proforma significantly improved the quality of emergency admission documentation in the neurosurgery unit. The findings support the broader adoption of such proformas across various medical specialties to enhance the accuracy, consistency, and reliability of clinical records, ultimately contributing to improved patient care and safety.